Information Support of High Schools in Corporate Library Network - Rakhmatullaev, Marat (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The paper includes information about some results of research on information library network of more than sixty Uzbekistan universities to provide them with scientific and educational information. It is being known there can be a great number of models of their realization and also their efficiency differs. Therefore, it is very important to find effective models of decision-making in information library network (ILN). At present time Cloud technologies have started to be developed actively both in corporate networks, and in global information environments. Use Cloud Computing in information-library networks can essentially raise efficiency as of user service, and of network administration. The experiments done in corporate network of academic libraries of Uzbekistan using ARMAT system have shown advantages of its applications.